Definition of a minimal region of deletion of chromosome 7 in uterine leiomyomas by tiling-path microarray CGH and mutation analysis of known genes in this region. - Vanharanta, S; Wortham, N; Langford, C; El-Bahrawy, M; van der Spuy, Z; Sjöberg, J; Lehtonen, R; Karhu, A; Tomlinson, I; Aaltonen, L (2007)
Somatic interstitial deletions of chromosome segment 7q22-q31 in uterine leiomyomas are a frequent event, thought to be indicative of a tumor suppressor gene in the region. Previous LOH and CGH studies have refined this region to 7q22.3-q31, although the target gene has not been identified. Here, we have used tiling-path resolution microarray CGH to further refine the region and to identify homozygous deletions in fibroids. Furthermore, we have screened all manually annotated genes in the region for mutations. We have refined the minimum deleted region at 7q22.3-q31 to 2.79 Mbp and identified a second region of deletion at 7q34. However, we identified no pathogenic coding variation.